A Cohort Study of Maternal Obesity and Breastfeeding Outcomes for Malay Women in Selangor, Malaysia - Abdul Hamid, Syahrul Bariah (Curtin University, 2016)
Breastfeeding is recommended for the optimal growth, development and health of infants. A prospective cohort study of 652 mothers was undertaken in Malaysia to investigate associations between maternal obesity and breastfeeding outcomes. Overweight and obese mothers had more difficulties in initiating breastfeeding initiation and they had a reduced duration of breastfeeding. The results are important for health promotion programs.